81.4k views
2 votes
2/3 x − 9 − 2x + 2 = 1 Which is an equivalent equation after combining like terms?

1 Answer

6 votes

Answer:

Any equation shown in the explanation

Explanation:

Hello!

Combining like terms means combining terms with the same variables.

So combing all x's, all y's, all numbers, etc.

2/3x - 9 - 2x + 2 = 1

combine the x's

-1 1/3 x - 9 + 2 = 1

combine normal numbers

-1 1/3 x - 7 = 1

Add 7 to both sides

-1 1/3x = 8

Make mixed number into improper fraction

-4/3x = 8

Multiply both sides by 3

-4x = 24

Divide both sides by -4

x = -6

The answer would be any of the equation I showed above

Hope this helps!

User Rluts
by
5.5k points